Computational modeling and experimental investigation of thread fatigue in ultra-high-pressure hydrogen storage vessels - Xue, Jiao; Zhang, Yanli; Li, Jing; Yin, Ruifeng (Frontiers in Applied Mathematics and Statistics, 2025)
This study presents a comprehensive computational and experimental investigation of thread fatigue behavior in ultra-high-pressure hydrogen storage vessels. A high-fidelity finite element model, incorporating axisymmetric assumptions and nonlinear material properties, is developed to simulate stress concentration and crack propagation under multiaxial cyclic loading. Crack growth is evaluated using an iterative fracture mechanics approach based on stress intensity factors, with polynomial fitting applied to characterize axial stress distributions. The influence of hydrogen embrittlement is explicitly considered in the fatigue life prediction through threshold-based stress intensity criteria. To validate the computational results, fatigue experiments are conducted on SA-372J steel vessels under controlled high-pressure hydrogen environments. The computational prediction indicated a fatigue life of approximately 613,190 cycles, while experimental results showed no measurable leakage or thread damage after 60,000 cycles, confirming excellent agreement and validating the model’s accuracy. This work establishes a reliable computational framework for predicting the fatigue life of threaded connections, offering valuable design insights to improve the safety and durability of hydrogen storage vessels operating under extreme service conditions.